A WRKY transcription factor, SlWRKY75, positively regulates tomato (Solanum lycopersicum L.) resistance to Ralstonia solanacearum - Chen, Na; Lv, Lingzeng; Duan, Lian; Wu, Jiajun; Shao, Qin; Li, Xiaopeng; Lu, Qineng (Frontiers in Plant Science, 2025)
WRKYs are a unique family of plant-specific transcription factors. Research has proven that WRKY transcription factors play essential roles in regulating plant growth and development as well as biotic and abiotic stress responses. However, the role of WRKY proteins in regulating the resistance of tomato (Solanum lycopersicum L.) to bacterial wilt caused by Ralstonia solanacearum remains unclear. Our previous study showed that R. solanacearum significantly upregulates SlWRKY75 expression in tomato. In this study, subcellular localization revealed that SlWRKY75 is located in the nucleus, while the transcriptional activation assay indicated that SlWRKY75 acts as a transcriptional activator. To investigate the functional role of SlWRKY75, we generated overexpression transgenic lines. After inoculation with Ralstonia solanacearum, these SlWRKY75-overexpressing plants displayed significantly enhanced resistance compared to the control plants. This enhanced resistance was supported by several physiological and molecular indicators: the transgenic plants showed better growth, elevated activity of key antioxidant enzymes, increased jasmonic acid (JA) accumulation, and upregulation of genes involved in JA biosynthesis and signaling. The SlWRKY75-overexpressing plants also showed decreased levels of hydrogen peroxide (H2O2), superoxide anion (O2–), and salicylic acid (SA) and decreased expression of SA synthesis-related and signal response-related genes. Meanwhile, knocking out of SlWRKY75 via CRISPR/Cas9 system resulted in an opposite trend. Yeast two-hybrid (Y2H) and co-immunoprecipitation (Co-IP) assays confirmed an interaction between SlWRKY75 and SlMYC2, wherein the SlWRKY75 binds to the W-box element in the SlMYC2 promoter and enhances its expression. These results indicate that the transcription factor SlWRKY75 positively regulates tomato resistance to bacterial wilt by enhancing the activities of antioxidants and disease resistance enzymes, regulating JA and SA signaling pathways, and modulating reactive oxygen species (ROS) homeostasis. Collectively, our findings not only elucidate a novel SlWRKY75-SlMYC2 regulatory module that fine-tunes hormone signaling and antioxidant defense in tomato immunity, but also highlight the potential of SlWRKY75 as a valuable gene resource for breeding bacterial wilt-resistant tomato cultivars.